1987
DOI: 10.1093/schbul/13.4.623
|View full text |Cite
|
Sign up to set email alerts
|

Orienting Response Research in Schizophrenia: Where We Have Come and Where We Might Go

Abstract: This review and critique of orienting response (OR) research in schizophrenia examines the initial Western work, outlines current positions, and notes several areas in which further lines of research are needed. Discussion involves characteristics of schizophrenic patients who are OR nonresponders; OR nonresponding as a possible trait marker; the question of OR nonresponding in child patients; the association between negative symptoms and OR nonresponding as well as the possible existence of a specific subgrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(40 citation statements)
references
References 133 publications
3
36
1
Order By: Relevance
“…, 1989) showed that both the auditory and visual P3 amplitudes in unmedicated schizophrenics negatively correlated with negative symptoms as assessed by the Brief Psychiatric Rating Scale (BPRS) (motor retardation, blunted affect, mannerisms and posturing, and emotional withdrawal). This is consistent with the proposal by Roth and Tinklenberg (1982), who argued that P3 is the ERP component most analogous to the skin conductance response, which like P3 is negatively correlated with negative symptoms (Bernstein, 1987).…”
Section: Neuroleptic and Clinical Correlates Of P3supporting
confidence: 92%
“…, 1989) showed that both the auditory and visual P3 amplitudes in unmedicated schizophrenics negatively correlated with negative symptoms as assessed by the Brief Psychiatric Rating Scale (BPRS) (motor retardation, blunted affect, mannerisms and posturing, and emotional withdrawal). This is consistent with the proposal by Roth and Tinklenberg (1982), who argued that P3 is the ERP component most analogous to the skin conductance response, which like P3 is negatively correlated with negative symptoms (Bernstein, 1987).…”
Section: Neuroleptic and Clinical Correlates Of P3supporting
confidence: 92%
“…It is also suggested that this development represents an adaptive or selfboredom during the course of their illness. However, it is important to acknowledge at protective mechanism that is designed to mitigate the effects of potentially stressful stimuthis juncture that in recent years there have been a number of psychosocial interventions lation (Bernstein 1987;Dawson and Nuechterlein 1984;Ohman 1981;Straube 1980; that have been shown to be effective in improving patients' competencies across a broad Straube and Ohman 1990). This proposal is strengthened by recent findings from animal spectrum of cognitive and psychosocial domains (e.g., Benton and Schroeder 1990; models, which suggest that stress-induced anhedonia (i.e., the inability to experience Berkke and Long 2000; Fenton and Schooler 2000; Mojtabai, Nicholson, and Carpenter pleasure and one of the more common and disabling negative symptoms) may be partly 1998).…”
Section: Of Psychotic Disordersmentioning
confidence: 99%
“…identify subjects whose trait and symptom characteristics may predispose them to schizophrenia or other psychopathology. Anhedonia is a classic negative symptom in schizophrenia, whereas perceptual aberration and magical ideation experiences exemplify mild to moderate positive symptoms~e.g., Bernstein, 1987;Meehl, 1964Meehl, , 1990Öhman, 1981;Zahn, 1986!. The dysthymia and hypomania0bipolar scales of the General Behavior Inventory~Depue & Klein, 1988;Depue, Krauss, Spoont, & Arbisi, 1989!…”
mentioning
confidence: 99%